Post - sedimentation influence on filtration capacity reservoir rock properties (Pur-Tazov oil\gas-bearing area) - Isaeva, Elena Rinatovna; Stolbova, Nellie Feodorovna; Dolgaya, Tatiana Fedorovna (IOP Publishing, 2015)
The processes of the second mineral formation (kaolinite, carbonates and micas) were identified during the post-sedimentation transformation studies in oil\gas deposits. Besides, quartz regeneration, solid product destructive formation processes and hydrocarbon oxidation processes were -determined. Correlation analysis of the mineralogy and petrophysics data revealed the post-sedimentation influence factors on the reservoir properties of deposits. It should be noted that the second kaolinite composition increase results in water saturation and density decrease, porosity and, especially, permeability increase. Quartz regeneration and second mica formation deteriorate the reservoir properties or poorly influence them. The hydrocarbon decay and oxidation products, as well as secondary carbonate seal the void space, replace the soluble rock debris and sharply deteriorate the reservoir properties of oil andgas deposits.
Keywords: осаждение; емкости; фильтрация; породы; корреляционный анализ; петрофизика; регенерация; коллекторские свойства; нефти; газовые месторождения